FORMULASI DAN EVALUASI SEDIAAN FACIAL WASH EKSTRAK MIMBA (Azadirachta indica A.Juss) - Caesa Anjarini, Saniyya; Kurniawari, Darini; Budi, Setia; Audina, Mia (Jurnal Insan Farmasi Indonesia, 2023)
Neem extract is known to have antibacterial activity against acne-causing bacteria. Neem extract is made into facial wash preparations to develop herbal plants into more modern preparations. This study aims to determine the optimal formulation from the results of the physical evaluation and hedonity test and then find out that there are differences from the results of the physical evaluation of neem extract (Azadirachta indica A.Juss) facial wash preparation. The research method used was a pre-experimental laboratory one-shot case study. Physical evaluation tests included organoleptic tests, homogeneity, pH, viscosity, free alkali, foam height/foam stability, free fatty acids and hedonity (favorability test). The results of the research on the organoleptic test obtained optimal results in formula 3 and the results of the homogeneity test obtained a homogeneous preparation. Optimal pH test results in formula 3. Optimal viscosity test results in formula 3. Free alkali test results from the three formulations did not contain free alkali. Optimal foam height/foam stability test results in formula 3. Free fatty acid test results do not meet SNI facial wash standards. The results of the hedonity test showed that formulation 3 was preferred by respondents. The optimal facial wash preparation is formulation 3.